Double workload: a study of the sexual division of labour among women telemarketing operators in Brazil. (1st July 2009) - Claudia Mazzei Nogueira,
Abstract : This paper discusses the sexual division of labour both in the workplace, that is, in the space of production, and in the home, which is termed the space of reproduction. The author discusses the close relationships that exist between the division of tasks in domestic labour of women workers and their functions in the world of work. The study draws on in-depth qualitative research in a telemarketing company. The aim of this study of telemarketing operators was to obtain a deeper understanding of how these workers experience the dimensions of their work in terms of the sexual division of labour in both production and reproduction. The term 'productive work is not used in the strict Marxist sense of work that directly creates surplus value but in a more generic sense, to designate the salaried act of working, whether in productive or unproductive work, as it is performed in capitalist society. The expression 'reproductive space' refers to the domestic sphere.